Modern Guidelines for Nutrition in Old Age: The Role of Preventive Diets in the Prevention of Chronic Diseases - Horváth, Brigitta; Szabó, Attila Péter; Savella, Orsolya (Magyar Gerontológia, 2025)
Increased life expectancy, coupled with declining fertility rates, is leading to a global demographic shift towards an ageing population. The number of older people (aged 60 and over) is expected to more than double by 2050 and more than triple by 2100. From an individual perspective, this is a positive development, but at the societal level it poses a number of challenges in terms of managing people’s health, quality of life, and economic circumstances. Although life expectancy is increasing, for many people the quality of life is declining, which can have a negative impact on both health and social institutions. The nutritional needs of older people differ from those of younger people, mainly due to age-related physiological changes. Their calorie requirements may decrease due to slower metabolism and reduced physical activity, but their requirements for certain macro- and micronutrients may increase. With advancing age, the risk of chronic diseases such as cancer, metabolic and cardiovascular diseases increas, as does the risk of osteoporosis, cognitive decline, and disability. In order to maintain health in old age and prevent the development of cardiovascular and metabolic diseases, it is important to reduce the intake of simple carbohydrates (to a maximum of 10% of total carbohydrate intake) and saturated fatty acids (to a maximum of 20–25 g per day), while ensuring adequate protein intake (1.0–1.2 g per kg of body weight) and consuming at least 400 g of fruit and vegetables per day. The salt intake of Hungarian seniors also significantly exceeds the recommended level (instead of 2 g per day, men over 65 consume 6.2 g and women consume 4.7 g), and fluid intake is insufficient, too (the recommended amount is 35 ml per kg of body weight). Among preventive strategies, nutrition is critical, yet it is currently underrepresented in the healthcare system and does not receive sufficient emphasis in care processes. A personalized healthy diet has significant benefits for older adults and can prevent, modify, or improve many age-related diseases and conditions. This review focuses on issues related to the nutrition and nutritional needs of older adults based on the latest guidelines. It also presents the most common complications resulting from poor nutrition and the possibilities for diet therapy.